GC-MS Analysis of Liposoluble Constituents of Different Parts of Dimocarpus longan - Zhang, Xiaowei; Cao, Wei; Wang, Yukun; Cun, Li; Wang, Siwang (Asian Journal of Chemistry, 2013)
The liposoluble constituents from the aril, husk and kernel of longan were studied. The gas chromatography-mass spectrometry (GC-MS) and computer spectrum searching technique were applied. 15, 34 and 33 compounds were identified from the petroleum ether extracts of the aril, husk and kernel of longan respectively. The study on the liposoluble constituents of the aril, husk and kernel of longan provided the test basis for the further development and utilization of Dimocarpus Longan Lour resources.